Sound characterizing using AI technique: article / Shahrul Rizal Johar - Johar, Shahrul Rizal (2003)
-This study concentrated on how to characterize sound signal using AI (Artificial Intelligence) technique. The software implemented was MATLAB Fuzzy Toolbox and MATLAB Simulink based on MATLAB 6.5 version. The sound or signal generated by the signal generator will be classified using simulation model developed in the MATLAB Simulink. The output result will be displayed in numerical form represented the frequency division e.g. VLF, LF, and MF etc.